Singaporeans’ preferences in public expenditures: exploratory happiness and well-being study - Neo, Xu Yi Nicolas (2016)
Happiness, though being the ultimate life goal for many people, is not easily defined or measured due to individual preferences. To discern what brings happiness to Singaporeans, this study aims to comprehend factors that affect their happiness from a public expenditure point of view, as most literatures focus solely on private consumption effects on happiness. After identifying the factors, the study proceeded to rank them according to public preferences. The method utilised in the study is the pairwise comparison approach using Dunn Rankin’s variance stable rank method - administered using MATLAB - which detects and controls for intransitivity and inconsistency. A total of 160 random participants were engaged for the preliminary pilot survey, and another group of 180 random participants took part in the MATLAB program. Contrary to expectations, the preliminary results indicate that transportation and environment are not considered top public expenditure factors that contribute to Singaporeans’ happiness. Instead, the top 6 factors are CPF, Security, Healthcare, Education, Family-focused Policy and Housing. As a result of the pairwise comparison, the study determines that Singapore government should focus on increasing public expenditures in the areas of Security and CPF, which will effectively increase citizens’ happiness. While 10-year average growth rates of Healthcare and Education expenditures reflect Singaporeans’ preferences, the results suggest that Singapore government should reduce or limit the growth of public expenditures on Housing and Family-focused policy. Instead, the funds for Housing and Family-focused policy could be channelled to higher valued areas of government expenditures. With this study, the government is equipped with a viable tool to have a better understanding on the analysis and implementation of future public policies - from the perspective of citizens’ happiness.